Manajemen Proyek Perancangan Taman Baca Masyarakat - Hardiansyah; Meri Hendayani; Ian Amukti Herlambang; Andhika Nove Rezki; Agung Wijoyo (CV. Multi Kreasi Media, 2022)
One way to educate the community is to build a library. However, services at libraries cannot reach all levels of society as well as TBMs that are very close to the community and the development of community reading parks that continue to grow in the South Tangerang area. Based on the results obtained, South Tangerang City, which is expected by the city government to become a Smart, Modern and Religious City, has spread and distributed TBMs in various parts and areas of South Tangerang City. All of these TBMs are programs of the South Tangerang City Library and Archives Department. TBMs have been advertised as very close to community libraries as they target community members, especially in areas where public libraries are difficult to reach. TBMs have organized various activities that arouse children's interest in reading, as well as activities that broaden their horizons. Common obstacles include minor issues such as the location of the building and desynchronization time between TBM service opening hours and children's learning, where most of their schools continue to implement Full Day School teaching.